Chikungunya Virus Infection in and Around Akola District, Maharashtra-Rising Trend Over a Decade - Nazneen I Malak; Sharmila S Raut; Seematai Prakash Katole; Nitin A Ambhore (RGUHS Journal of Medical Sciences)
Background Chikungunya is a viral fever caused by an arbovirus belonging to the genus Alphavirus transmitted to humans through the bite of the Aedes aegypti mosquito. It is a serious public health issue characterized by a sudden rise in temperature acute arthralgia and rash.Aim To estimate the seropositivity of Chikungunya infection in suspected patients and also to analyze the seasonal trends and clinical manifestations of the infection.Methods A total of 13554 serum samples from suspected Chikungunya cases were received between January 2015 and April 2024 by the Microbiology laboratory at a tertiary care hospital from patients in and around the Akola district. The samples were then tested for Chikungunya IgM antibody using IgM antibody capture ELISA kit NIV CHIK IgM developed by National Institute of Virology Pune India.Results Of the 13554 serum samples received 794 5.86 were tested positive for Chikungunya IgM antibody ELISA. The highest positivity was found in the 21-30 year age group 23.8 with a female preponderance 53.65. A peak in incidence was noted in the month of October 27.95 followed by November 14.23. All the positive patients presented with fever and joint pain.Conclusion A rising trend in seropositivity was observed in and around Akola district over the past decade. This reiterates the fact that Chikungunya remains a major health concern in our region and highlights the need for regular surveillance and timely laboratory testing of suspected cases to reduce the disease burden and severity.